Selectivity of the CUBAN domain in the recognition of ubiquitin and NEDD8. (5th February 2019) - Castagnoli, Luisa; Mandaliti, Walter; Nepravishta, Ridvan; Valentini, Eleonora; Mattioni, Anna; Procopio, Radha; Iannuccelli, Marta; Polo, Simona; Paci, Maurizio; Cesareni, Gianni; Santonico, Elena
Abstract : Among the members of the ubiquitin‐like (Ubl) protein family, neural precursor cell expressed developmentally down‐regulated protein 8 (NEDD8) is the closest in sequence to ubiquitin (57% identity). The two modification mechanisms and their functions, however, are highly distinct and the two Ubls are not interchangeable. A complex network of interactions between modifying enzymes and adaptors, most of which are specific while others are promiscuous, ensures selectivity. Many domains that bind the ubiquitin hydrophobic patch also bind NEDD8 while no domain that specifically binds NEDD8 has yet been described. Here, we report an unbiased selection of domains that bind ubiquitin and/or NEDD8 and we characterize their specificity/promiscuity. Many ubiquitin‐binding domains bind ubiquitin preferentially and, to a lesser extent, NEDD8. In a few cases, the affinity of these domains for NEDD8 can be increased by substituting the alanine at position 72 with arginine, as in ubiquitin. We have also identified a unique domain, mapping to the carboxyl end of the protein KHNYN, which has a stark preference for NEDD8. Given its ability to bind neddylated cullins, we have named this domain CUBAN (Cullin‐Binding domain Associating with NEDD8). We present here the solution structure of the CUBAN domain both in the isolated form and in complex with NEDD8. The results contribute to the understanding of the discrimination mechanism between ubiquitin and the Ubl. They also provide new insights on the biological role of a ill‐defined protein, whose function is hitherto only predicted. Abstract : Identification of a novel domain, named CUBAN (Cullin‐Binding domain Associating with NEDD8) mapping at the C‐terminal end of KHNYN protein, which shows a stark preference for NEDD8 and neddylated cullins. The solution structure of CUBAN in complex with NEDD8 shows that the interacting surface does not involve the 'canonical' Ile44‐centred hydrophobic patch.